2023
DOI: 10.3389/fsufs.2023.1188159
|View full text |Cite
|
Sign up to set email alerts
|

Physiology and proteomics analyses reveal the regulatory mechanism of mepiquat chloride in soybean

Abstract: Soybean is an important grain and oil crop cultivated worldwide. Mepiquat chloride (DPC), a plant growth regulator, is widely used in cotton planting; however, its application in soybean remains rarely studied. Herein, we explored DPC regulation in soybeans using morphology, physiology, and proteomics analyses. Morphological and physiological analyses showed that DPC significantly reduced the plant height and shoot dry weight, promoted the growth of lateral roots in a specific concentration range, increased th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…The hormones MT and MC have been recently found to be among cotton’s most efficient abiotic stress signaling regulators [ 1 , 14 ]. As a result of suppressing gibberellin (GA) production in plants, it has been shown that MC improves cotton yield by reducing leaf area and plant height and reducing the length of shoots and fruit branches [ 15 , 16 , 17 ]. Applying MC affects the physiological characteristics of cotton leaves [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The hormones MT and MC have been recently found to be among cotton’s most efficient abiotic stress signaling regulators [ 1 , 14 ]. As a result of suppressing gibberellin (GA) production in plants, it has been shown that MC improves cotton yield by reducing leaf area and plant height and reducing the length of shoots and fruit branches [ 15 , 16 , 17 ]. Applying MC affects the physiological characteristics of cotton leaves [ 18 ].…”
Section: Introductionmentioning
confidence: 99%